2019
DOI: 10.3390/coatings9120857
|View full text |Cite
|
Sign up to set email alerts
|

The Excitation of Ultrasound by Laser Radiation in Water Using an Optical Fiber Laser Converter with a 2D Colloidal Crystalline Coating

Abstract: The technology of applying a colloidal single-layer coating of transparent polystyrene (PS) Ø 1 μm spheres at the tip face of a quartz fiber has been proposed and tested. Such a coating plays, in a light absorbing liquid, the role of a converter of pulsed laser radiation into acoustic radiation. The generation of ultrasound in water using a converter based on a quartz fiber 1 mm in diameter with a 2D colloidal crystalline coating consisted of polystyrene spheres with a diameter of ~1 μm at the fiber end was in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…A methodology for calculating the main characteristics of the generated ultrasound (the frequency spectrum and the angular diagram) is presented (Part 2). Part 3 (Results) contains the results of calculating US parameters in two opposite cases: large spheres with a diameter of 200 µm in a highly absorbing medium (ink solution in water at a wavelength of 0.532 µm, light absorption coefficient α ≈ 10 −2 µm −1 ) and small spheres with a diameter of ≈ 1 µm in a weakly absorbing medium (pure water at a wavelength of 1.064 µm, α ≈ 10 −5 µm −1 ), as well as comparison of the results of calculations with the corresponding experimental results from the papers [8,9]. Part 4 (Discussion) is devoted to the analysis of the comparison of theoretical and experimental results both from the point of view of the applicability of the theoretical consideration and from the viewpoint of the possibilities and prospects for the development of ultrasound generation technology using fiber systems coated by transparent spheres.…”
Section: Of 14mentioning
confidence: 93%
See 4 more Smart Citations
“…A methodology for calculating the main characteristics of the generated ultrasound (the frequency spectrum and the angular diagram) is presented (Part 2). Part 3 (Results) contains the results of calculating US parameters in two opposite cases: large spheres with a diameter of 200 µm in a highly absorbing medium (ink solution in water at a wavelength of 0.532 µm, light absorption coefficient α ≈ 10 −2 µm −1 ) and small spheres with a diameter of ≈ 1 µm in a weakly absorbing medium (pure water at a wavelength of 1.064 µm, α ≈ 10 −5 µm −1 ), as well as comparison of the results of calculations with the corresponding experimental results from the papers [8,9]. Part 4 (Discussion) is devoted to the analysis of the comparison of theoretical and experimental results both from the point of view of the applicability of the theoretical consideration and from the viewpoint of the possibilities and prospects for the development of ultrasound generation technology using fiber systems coated by transparent spheres.…”
Section: Of 14mentioning
confidence: 93%
“…No detailed enough research aimed at testing and exploiting such ideas has been reported in the literature yet. In our earlier works [8][9][10][11], we carried out experimental studies in two relatively limiting cases: large spheres with a diameter of 200 µm in a highly absorbing medium (ink solution in water at a wavelength of 0.532 µm, light absorption coefficient α ≈ 10 −2 µm −1 ), and small spheres with a diameter of 0.96 µm in a weakly absorbing medium (pure water at a wavelength of 1.064 µm, α ≈ 10 −5 µm −1 ). The considered media were chosen because they are the simplest phantoms of biological media.…”
Section: Of 14mentioning
confidence: 98%
See 3 more Smart Citations